Platelet-Rich Plasma for the Treatment of Androgenic Alopecia: A Systematic Review - Chen, Jenny X.; Justicz, Natalie; Lee, Linda N. (Facial Plastic Surgery, 2018)
The use of platelet-rich plasma (PRP) has become increasingly commonplace in facial plastic surgery for the treatment of androgenic alopecia (AGA). However, this treatment remains novel with a range of application techniques and outcomes described in the literature. Herein, the authors systematically review the existing literature on the use and efficacy of PRP for AGA. Systematic review of PubMed, Embase, and Cochrane databases was performed. Case reports were excluded. Twenty-four papers met inclusion criteria for this study: 8 randomized control trials and 16 prospective cohort studies. Twenty-one studies used clinical criteria to diagnose AGA, while three used confirmatory biopsies. PRP was injected with or without the use of a numbing agent, and most studies performed multiple injections (three or more separated by several weeks). Twenty-one studies reported positive outcomes by objective criteria (88%), while three suggested that there was no clinical improvement, although in two of these studies patients still reported increased satisfaction. There were no complications reported other than transient edema/erythema and pain/headache associated with the procedure. The existing literature suggests that PRP is a low-risk intervention to treat AGA associated with good patient satisfaction and objective improvements in outcomes. Further research is needed to optimize preparation and delivery methods as well as standardize measurements of clinical outcomes.
Keywords: hair loss; hair density; growth factors; platelet rich plasma; androgenic alopecia